PERANCANGAN DAN PEMBANGUNAN SISTEM INFORMASI PENGELOLAAN JEMAAT GBKP BERBASIS WEB - Jean Sontri Ananta; Ramos Somya (J-ICON : Jurnal Komputer dan Informatika, 2023)
A web-based information system is a technology that can be utilized for data archiving. Archiving data such as church congregations is crucial for the development of the church. However, one of the churches, the Batak Karo Protestant Church (GBKP), still archives data using books and Microsoft Excel. GBKP's data archiving using books and Microsoft Excel is still not efficient and effective when moving congregations, where a letter of request is submitted in writing by the church of origin to the church of destination. This research aims to implement a web-based information system that can provide congregational data management and transfer features to assist churches in conducting data processing more effectively and efficiently. The method applied in the design process to system implementation is the waterfall method and the development of information systems using the PHP, HTML, CSS and JavaScript programming languages. Testing in this study was carried out using the User Acceptance Test (UAT) method, namely the alpha and beta testing. In alpha testing, information is obtained that 100% of the functions are compliant or running well. In beta testing, it was concluded that this information system could provide convenience for churches in managing data, especially when moving congregations between churches, because the beta testing results reached a value of 95%. This web-based information system is proven to have a function that can provide convenience to churches in managing data and assist churches and congregations in moving because sending data and creating documents can be done quickly.